Efficient synthesis of Triazolo[4,5-d]pyrimidine-7-carbonitriles and Imidazole-4,5-dicarbonitriles using Triethylorthoalkylates and their structural characterisation by Single-crystal x-ray diffraction - Amal Al-Azmi; Mickey Vinodh (Kuwait Journal of Science)
Abstract